Lighthill’s Theory of Sound Generation in Non-Isothermal and Turbulent Fluids - Swati Routh; Zdzislaw E. Musielak (Fluids, 2025)
Lighthill’s theory of sound generation was developed to calculate acoustic radiation from a narrow region of turbulent flow embedded in an infinite homogeneous fluid. The theory is extended to include a simple model of non-isothermal fluid that allows finding analytical solutions. The effects of one specific temperature gradient on the wave generation and propagation are studied. It is shown that the presence of the temperature gradient in the region of wave generation leads to monopole and dipole sources of acoustic emission and that the efficiency of these two sources may be higher than Lighthill’s quadrupoles. In addition, the wave propagation far from the source is different than in Lighthill’s original work because of the presence of the acoustic cutoff frequency resulting from the temperature gradient.